PELAKSANAAN PENYELENGGARAAN PERIZINAN BERUSAHA DI KABUPATEN INDRAGIRI HILIR BERDASARKAN PERATURAN DAERAH KABUPATEN INDRAGIRI HILIR NOMOR 7 TAHUN 2017 TENTANG PENYELENGGARAAN PELAYANAN TERPADU SATU PINTU - Sulaiha Sulaiha; Gusliana HB; Zainul Akmal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Licensing in Indragiri Hilir is fully implemented Online Single Submission(OSS) and licensing in Indragiri Hilir is fully implemented Online SingleSubmission (OSS) as well as conducted based Online Single Submission RiskBased Approach (OSS-RBA) in accordance with Government Regulation Number5 of 2021 concerning Implementation of Risk-Based Business Licensing. OSS RBAis a business license granted to business actors to start and run their businessactivities which are assessed based on the risk level of a business. In TembilahanCity there are several obstacles in the implementation of based licensing OnlineSingle Submission (OSS) as in terms of services and infrastructure.The purpose of this research is to find out the implementation of businesslicensing in Indragiri Hilir Regency, Obstacles in the implementation of businesslicensing and to find out the efforts made by the investment service and one-doorintegrated services in improving business licensing services in Indragiri HilirRegency. This type of research is research using legal research methods using asociological juridical approach in which the author tries to collect data andinterview writing sources which are divided into primary, secondary and tertiarydata.The implementation of risk-based business licensing in Indragiri HilirRegency is fully implemented based on Government Regulation Number 5 of 2021concerning the implementation of risk-based business licensing, in theimplementation of licensing there are several obstacles such as the unavailabilityof online signatures, there are still many permit applicants who do not understandhow to register online so choose to register offline and come directly to theinvestment service and one-stop integrated services. Facilities and infrastructurethat are still not in accordance with applicable laws and knowledge and ability toaccess OSS RBA are still at different levels. To overcome this problem, theinvestment service and one-stop integrated services have made innovations calledJAPRI and SIMPATI which are hoped with this system can facilitate the businesslicensing process in Indragiri Hilir district. Suggestions for socialization tobusiness actors regarding government regulation number 5 of 2021 andprocedures for registering permits online with SIMPATI.Keywords: Licensing, Public Service, OSS.